Development of Writing Instrument Through Describtive Paragraph Web.Blog Bassed - elia elia santi (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2019)
Assessment of learning outcomes is one of the important activities in the world of education as explained in Permendikbud No. 23 of 2016, assessment is the collection and processing of information to measure the achievement of student learning outcomes. This research produces a product in the form of blog media as a guide to improve the ability to write and create web. Blog. Blogs can be accessed anywhere and anytime, as long as they are connected to the internet network. The material in this blog is tailored to the needs of written material for middle school students. Blog material is also validated through three aspects. These three aspects were validated by material experts, trainers, and participants in writing activities. The first aspect is the clarity of the material delivered. The validation results show an 80% number which means that the material delivered is clear. The second aspect is communicative language and ease of understanding. The validation results show 81% which means that the language on the blog is very communicative, making it easy for users to understand. The last aspect is the suitability of the material with the aim of journalistic extracurricular guidance. The validation results show 77% which means that the material is in accordance with the purpose of writing skills.